Tarqiyah al-Tafkīr al-Naqdiy fi al-Kitābah al-‘Arabiyyah al-Ibdā’iyyah min Khilāl al-Ta’allum al-Qāim alā al-Mashārī’ (PJBL) li Ṭālibāt al-Ṣaf al-Thālith fi Madrasah Manba’i al-Ṣālihīn al-Āliyah Gresik - Mohammad Makinuddin; Ummu Khofiyah (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
Arabic language instruction in traditional Islamic schools often relies on conventional methods like lectures and memorization, which fail to develop students' critical thinking and creative writing abilities. This study investigated the effectiveness of Project-Based Learning (PjBL) in enhancing critical thinking through Arabic creative writing among third-grade students at Madrasah Aliyah Manba'ul Sholihin, Gresik. Using a quasi-experimental design, 120 students were divided into three groups: collaborative PjBL (IPA3), individual PjBL (IPA4), and a control group (IPK6) with conventional instruction. Results demonstrated significant improvements in the experimental groups: the collaborative group's average score increased by 21 points (60 to 81), the individual group by 13.27 points (56 to 69.27), while the control group showed minimal improvement (7.73 points, from 54 to 61.73). Statistical analysis (ANOVA: F=47.528, p=0.000) confirmed significant differences between groups, with post-hoc tests validating differences between all pairs. The findings indicate that PjBL significantly enhances critical thinking skills in Arabic creative writing, particularly in writing structure, vocabulary usage, and logical analysis. This research concludes that PjBL effectively improves Arabic language learning quality by making it more contextual and interactive. The study recommends integrating PjBL into madrasah curricula to equip students with higher-order thinking skills essential for 21st-century challenges.